(untitled) (International Journal of Economics Management and Social Science, 2026)
Background: The intensification of industrial capitalism has transformed the structural basis of social cohesion, raising fundamental questions about how modern societies sustain solidarity under conditions of radical differentiation, individualism, and normative pluralism. Émile Durkheim’s foundational distinction between mechanical and organic solidarity remains one of sociology’s most enduring analytical frameworks for addressing these questions. Objective: This paper examines the continued relevance of Durkheim’s solidarity typology for understanding social cohesion in contemporary industrial and post-industrial societies. Methods: A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar, covering peer-reviewed publications from 2019 to 2025 on Durkheimian sociology, social cohesion, anomie, and industrial society. Results: The findings demonstrate that Durkheim’s framework retains significant explanatory power for analyzing contemporary social disintegration, anomie, the crisis of collective identity, and the fragility of civic solidarity in pluralist democracies. However, the framework requires critical extension to accommodate digital social bonds, multicultural solidarity, and neoliberal atomization. Conclusion: Durkheim’s solidarity theory provides an indispensable starting point for sociological analysis of social cohesion, but must be critically updated to account for the structural transformations of late modernity, including digital connectivity, cultural hybridity, and global economic integration. Keywords: Durkheim, mechanical solidarity, organic solidarity, social cohesion, anomie, industrial society, division of labor